A modified low profile patch antenna with enhanced bandwidth for multiband applications - Samantaray D.; Bhattacharyya S. (My University, 2025)
This paper presents on the design and working analysis of a modified compact patch antenna with enhanced bandwidth for X/Ku/K/Ka-band applications. Four square cuts at the four corner of the patch and slits at three faces have been incorporated in this configuration to enhance the bandwidth as well as gain of the antenna. The antenna modelling is carried out according to arrangements and procedure so that it works over the multiple frequency bands viz., 10.05-11.85 GHz, 15.37-16.17 GHz and 17.10-34 GHz. The maximum return loss of 40 dB has been obtained at 25.36 GHz while the maximum gain of 7.12 dBi has been realized at the same operating frequency and also it exhibits endfire radiation characteristics. This antenna can be employed for X/Ku/K/Ka band applications like radar, molecular rotational spectroscopy and satellite communication. © 2019 IEEE.